2018
DOI: 10.1080/02615479.2018.1433157
|View full text |Cite
|
Sign up to set email alerts
|

Working with the enemy? Social work education and men who use intimate partner violence

Abstract: The accurate measurements of natural and anthropogenic aerosol particulate matter (PM) is important in managing both environmental and health risks; however, limited monitoring in regional areas hinders accurate quantification. This article provides an overview of the ability of recently launched geostationary earth orbit (GEO) satellites, such as GOES-R (North America) and HIMAWARI (Asia and Oceania), to provide near real-time ground-level PM concentrations (GLCs). The review examines the literature relating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 158 publications
(206 reference statements)
0
8
0
Order By: Relevance
“…Social workers engage with many different service users, with some accessing services voluntarily and others being mandated through various legislative or social processes to engage with services. Men who use IPV are often considered to be mandated or involuntary service users (Jury and Boxall, 2018). There has been little research regarding student perspectives of the involvement of involuntary service users in social work education.…”
Section: Student Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Social workers engage with many different service users, with some accessing services voluntarily and others being mandated through various legislative or social processes to engage with services. Men who use IPV are often considered to be mandated or involuntary service users (Jury and Boxall, 2018). There has been little research regarding student perspectives of the involvement of involuntary service users in social work education.…”
Section: Student Perspectivesmentioning
confidence: 99%
“…Authors such as Smith (2013) and Raikes and Balen (2016) have discussed the perspectives of service users with complex issues who are involved in social work education, but no previous research has been identified that explores the perspectives of men who use IPV regarding their possible involvement in social work education. It has, however, been suggested that men who use IPV could make a positive contribution to social work education (Jury and Boxall, 2018).…”
Section: Service User Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations